Ventilation for environmental tobacco smoke - Rock, Brian A. (Brian Allan) (Elsevier Butterworth-Heinemann, 2006)
Odor and irritation play a prominent role in the quality of air when tobacco smoke (ETS) is present within a building. Ventilation for Environmental Tobacco Smokewas written to educate companies about obstructed ventilation systems due to tobacco smoke within their facilities. It is a guide that HVAC designers can use to provide better, more efficient units for ventilate, thus creating higher optimized air quality, comfort, and energy use. Many HVAC(heating, ventilating, and air-conditioning)designers have few guides to follow for providing efficient systems to handle ETS problems. This design guide primarily focuses on the design structure of units and less on the requirements according to codes and guidelines. With the proper guidance, HVAC designers will be insured to produce a highly efficient system that will reassure companies and clients that they are receiving quality ventilation flow. This guide can be used as an introductory on ETS, as a refresher to those within the HVAC industry, a tool to stimulate more discussion and research, as well as a reference for architects and building owners who are already experienced on ETS concerns. * Presents background information on HVAC * Provides an overview of what factors affect indoor environmental quality and methods for estimating needed ventilation rates * Contains design issues and examples for various applications, along with summaries.